2010
DOI: 10.1016/j.nurt.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Immune Dysfunction in Autism: A Pathway to Treatment

Abstract: Summary: Autism is a complex and clinically heterogeneous disorder with a spectrum of symptoms. Clinicians, schools, and service agencies worldwide have reported a dramatic increase in the number of children identified with autism. Despite expanding research, the etiology and underlying biological processes of autism remain poorly understood, and the relative contribution from genetic, epigenetic, and environmental factors remains unclear. Although autism affects primarily brain function (especially affect, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 131 publications
4
105
1
6
Order By: Relevance
“…Whereas evidence suggests that there may be altered immune system function in some children with ASD, the specific alterations appear to vary across studies and will require further analysis to reach consensus [43]. Autism biomarkers were identified that could be categorized according to the key theories that exist regarding the etiology of autism: gastrointestinal factors, immune dysregulation, heavy metal toxicity, neurotransmitter abnormalities, and oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas evidence suggests that there may be altered immune system function in some children with ASD, the specific alterations appear to vary across studies and will require further analysis to reach consensus [43]. Autism biomarkers were identified that could be categorized according to the key theories that exist regarding the etiology of autism: gastrointestinal factors, immune dysregulation, heavy metal toxicity, neurotransmitter abnormalities, and oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that there is a decline occur on anti -inflammatory cytokine levels such as IL -10 and transforming growth factor beta (TGF-β) on autistic individuals. However, in all studies made in this field no consistent results in terms of cytokine patterns could be provided (Careaga et al 2010). Studies in which an increase on autoantibody unique to the brain is indicated support the autoimmune mechanism.…”
Section: Wwwintechopencommentioning
confidence: 95%
“…In autism, there is an increase in the proinflammatory chemokines and modulator cytokines (Cohly and Panja 2005). Detected increase in the level of proinflammatory cytokines such as IL -6, TNF -alpha and monocyte chemoatractan protein 1 (MCP -1) in the brain samples and cerebrospinal fluid indicates that active neural inflammatory process is continuing in autism (Careaga et al 2010). TNF-alpha is a strong immunomodulatory cytokine that is produced by macrophages and partly by active T cells.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations